Al Bai Bithaman Ajil in abandoned housing projects: legal perspectives, practices & recommendations / Mohamad Lusfi Yaakob - Yaakob, Mohamad Lusfi (2020)
Al Bai Bithaman Ajil contract, an Islamic financing product invented and practiced by Malaysian banks, has emerged as a source of disputes between banks and customers as the claim for balance of selling price in abandoned housing projects cases proved to be unfair and burdening the customers. The problems of balance of selling price invited different views from Islamic scholars as well as judges pertaining to the rights of the bank to the balance of selling price. There is a need to review the performance of the obligation to pay the balance of selling price in abandoned housing projects particularly as there is no provision in the Al Bai Bithaman Ajil contract itself to deal with such unfortunate situation that befell the customers. This research intends to study whether the applicability of common law principles to the claim by the bank for full selling price under Al Bai Bithaman Ajil contract without the delivery of the house reflects the intention of the parties and whether under common law the claim by the bank for full selling price without the delivery of the house is truly justified. This study adopts library-based research methodology by examining the law, principles, concept, theories and doctrines of Al Bai Bithaman Ajil contract referring to primary material such as statutes including the Islamic Financial Services Act 2013 and court decisions as well as secondary materials such as books, articles and past theses. The common law principles, concept, theories and doctrines were analyzed with the aim to focus on the claim for the balance of the purchase price upon partial disbursement of bank’s buying price to evaluate the reasonability of demanding the payment of selling price in abandoned housing projects. The analysis carried out support the contention that demanding balance of selling price despite the non-delivery of the subject matter is unfair and against the common law and Islamic principles. This study concludes that balance of selling price in non-delivery of house due to abandoned housing project is a critical issue as customer as customer had to pay profit to the bank inconsistent with the principles of law and against the tradition of the Prophet (peace be upon him) that prohibited the sale of non-existent subject matter. For that reason, this research recommended that the courts to consider the application doctrine of frustration to prevent injustice due to the impossibility of performing the contract which would cause unfairness to the parties.